(untitled) (Asian-Australasian Journal of Food Safety and Security, 2018)
The objectives of this study were to assess the bacteriological quality of tap water samples obtained from different markets of different upazillas of Mymensingh, Sherpur & Gazipur district. For achieving the above mentioned objectives, methods of heterotrophic plate count (HPC) and total coliform count (TCC) were applied. Moreover, isolated E. coli from tap water samples were characterized by using biochemical test, molecular method and antimicrobial susceptibility tests. HPC was highest in market tap water collected from Kaligonj and TCC was highest in market tap water of collected from Mymensingh sadar. The geometric mean of HPC of Mymensingh, Gazipur and Sherpur districts water was 8.4x105, 2.5 x106 and 6.8 x105 C.F.U/100 ml. All isolates of E. coli (n=20) were amplified by using 16S rRNA gene based PCR. In respect to antimicrobial susceptibility testing, most of the E. coli isolates were susceptible to norfloxacin, ampicilin, tetracycline, streptomycin and ciprofloxacin. Furthermore, a few E. coli isolates were intermediate resistant to gentamycin and ciprofloxacin. However, a few of the E. coli isolates were resistant to erythromycin and amoxycilin. Moreover, out of 20 E. coli isolates 3 (15%) isolates were detected as multidrug resistant. This study indicated the presence of multidrug resistant E. coli isolates in tap water in Mymensingh, Sherpur and Gazipur districts that warrants particular attention. Asian Australas. J. Food Saf. Secur. 2018, 2(1), 21-28